Separating the effects of air and soil temperature on silver birch. Part I. Does soil temperature or resource competition determine the timing of root growth?. (8th August 2022) - Kilpeläinen, Jouni; Domisch, Timo; Lehto, Tarja; Piirainen, Sirpa; Silvennoinen, Raimo; Repo, Tapani
Abstract: The aboveground parts of boreal forest trees mostly grow earlier, and the roots later, in the growing season. We aimed to experimentally test whether the extrinsic driver of soil temperature or the intrinsic driver (resource competition between plant parts) is a more important control for the root and shoot growth of silver birch ( Betula pendula Roth) seedlings. Sixteen two-year-old seedlings were grown in controlled environment rooms for two simulated growing seasons (GS1, GS2). In GS1, all the seedlings were acclimatized under the same conditions, but in GS2, the soil temperature treatments were: (i) constant 10 °C (Cool); (ii) constant 18 °C (Warm); (iii) early growing season at 10 °C, switched to 18 °C later (Early Cool Late Warm, ECLW) and (iv) early growing season 18 °C, switched to 10 °C later (Early Warm Late Cool, EWLC). The treatments did not affect growth allocation between shoots and roots. Warm soil benefitted shoot elongation as it slowed down in EWLC and accelerated in ECLW after the soil temperature switch. However, whole-tree biomasses were similar to Cool and the seedlings grew largest in Warm. Phenology was not strongly affected by soil temperature, and root and shoot growth did not usually peak simultaneously. Short root mortality increased strongly in ECLW and decreased in EWLC after the soil temperature switch. Long root longevity was not significantly affected but long root growth ceased earliest in ECLW. Soil warming increased foliar nutrient contents. Growth dynamics were not solely driven by soil temperature, but resource competition also played a significant role. The study showed the importance of soil temperature for fine root dynamics not only through root growth but also via root mortality, as soil warming increased mortality even more than growth. Soil temperature has complex effects on tree and soil functioning, which further affects carbon dynamics in forest ecosystems that have a climate feedback.